KELAYAKAN BUKU TEKS BAHASA INDONESIA TERBITAN BALITBANG KEMDIKBUD DENGAN KURIKULUM 2013 REVISI 2016 - Muchti, Andina; Dewi, Yuni Citra (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Media and learning resources are the core components of teaching activities. Learning resources is related to textbooks as learning materials for students and teachers to provide additional knowledge. This study aims to see the feasibility of buku teks Bahasa Indonesia Class VII published by Balitbang Kemdikbud with the kurikulum 2013 revision  2016, which is to determine whether the book is really qualified so worthy to be used as a source of learning. The feasibility is reviewed in terms of content and language . From the analsys the aspect of content, the material is in accordance with KI and KD in  the curriculum 2013. While viewed from the aspect of language, textbooks Indonesian Class VII Curriculum 2013 Revision 2016 is good and not complicated language, careful choice of words, language which is used easily understood, but  there is a vocabulary that does not conform to the general rules of Ejaan Bahasa Indonesia.